The Role of Technology in Inclusive Education: Challenges and Opportunities in Developing Countries - Kushariyadi, Kushariyadi; Mustofa, Mustofa; Permatasari, Armita; A. Fitriani; Faridah, Luluk (International Journal of Educational Research Excellence (IJERE), 2024)
The objective of inclusive education is to guarantee that every individual, irrespective of physical, intellectual, social or emotional limitations, is provided with equal access to educational opportunities. The advent of technology has led to the emergence of new possibilities for the implementation of inclusive education, particularly in resource-constrained developing countries. However, the implementation of technology in inclusive education in developing countries is confronted with a multitude of challenges, encompassing deficiencies in infrastructure and constraints in educator training. This article seeks to examine the role of technology in inclusive education in developing countries and identify the challenges and opportunities that arise. The research employs a literature review methodology to collate data from pertinent studies and proffer policy recommendations to enhance the role of technology in inclusive education.